2019
DOI: 10.1177/2041669519870553
|View full text |Cite
|
Sign up to set email alerts
|

The Recognition of Solid Object Shape: The Importance of Inhomogeneity

Abstract: A single experiment evaluated the haptic-visual cross-modal matching of solid object shape. One set of randomly shaped artificial objects was used (sinusoidally modulated spheres, SMS) as well as two sets of naturally shaped objects (bell peppers, Capsicum annuum and sweet potatoes, Ipomoea batatas ). A total of 66 adults participated in the study. The participants’ task was to haptically explore a single object on any particular trial and subsequently indicate whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Almost all surface regions on naturally occurring solid objects are either saddle-shaped ( hyperbolic ), bump- or dimple-like ( elliptic ), or cylindrical ( parabolic ). Many researchers have hypothesized that solid object shape is represented 34 38 as spatial configurations of these types of surface regions. In our current stimulus displays, only small portions of the objects are visible at any given time because of occluding surfaces (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all surface regions on naturally occurring solid objects are either saddle-shaped ( hyperbolic ), bump- or dimple-like ( elliptic ), or cylindrical ( parabolic ). Many researchers have hypothesized that solid object shape is represented 34 38 as spatial configurations of these types of surface regions. In our current stimulus displays, only small portions of the objects are visible at any given time because of occluding surfaces (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, parabolic surface regions are shaped like cylinders (curved in one direction, but not curved in a perpendicular direction). As an example, consider the solid object shown in Figure 3; this is a sweet potato (Ipomoea batatas) that I purchased in a grocery store and then laser-scanned in 3-D (Norman et al, 2019). This sweet potato has three prominent elliptic regions (indicated by green & blue) and two hyperbolic ones (indicated by red).…”
Section: Palabras Clavementioning
confidence: 99%
“…We used a dissimilarity task over alternatives like object recognition or haptic search (van Polanen et al, 2014) for two reasons: First, we reasoned that dissimilarity tasks would be less susceptible to pop-out effects where specific features of objects can be used as cues to make judgments, thus ensuring that subjects attend to the whole object. It has been shown that pop-out effects indeed exist for both alternatives (Norman et al, 2019; van Polanen et al, 2014). Second, the dissimilarity rating paradigm can be used to quantitatively assess how two sources of information are combined, unlike recognition rates or search time, which exhibit a much more complex relationship with the sensory evidence.…”
Section: Introductionmentioning
confidence: 99%